Boerka Goat: A Meat Type Goat of Boer X Kacang Crossbred - Ginting, Simon P; Mahmilia, Fera (Indonesian Bulletin of Animal and Veterinary Sciences, 2008)
The world goat population has for three main types, namely meat goats, dairy goats and fiber goats. In Indonesia, goat meat is produced mainly the Kacang goat, a small-size type with low growth rate, but prolific. The development of new goat breed with Â larger Â mature Â weightÂ  andÂ  greater Â growthÂ  rateÂ  is important Â to Â promote Â and Â increaseÂ  the Â goat Â meat productionÂ  and consumption as well. The acceleration of meat goat production in Indonesia need to be stimulated due to the large potential of the international market. The healthy goat meat due to its higher polyunsaturated to saturated fatty acid ratio compared to those of beef or lambs should be more promoted to encourage the consumption rate. The Boerka goat which has been developed by mating the male Boer goat to Kacang does has good characteristics of meat goat type. The average birth weight, weaning weight, weight at 6, 9, 12, 18 months old, and mature weight of Boerka goats are greater 33 â 48% compared to those of Kacang goat. The average pre-weaning (0 â 90 days) and post-weaning growth rate (3 â 12 months) of Boerka in average are 39 and 46%, respectively higher than those of Kacang goats. Under intensive management system, the kidding interval is 233 days, equal to that of Kacang goat. Carcass characteristics such as carcass weight and length are greater in Boerka compared to Kacang goat. The pH and protein content of carcass are comparable, while the fat content is lower in Boerka carcass. It is important to design proper schemes for the dissemination of this Boerka goats to stakeholders. These schemes should be able to provide the Boerka goats in a sustainable pattern, so that the production, supply and quality of this crossbred goat could be maintained continuously. Several alternative schemes based on the nucleus-based breeding principles are proposed and discussed. Â  Key words: Goat, meat type, crossbreeding, development